Maqasid al-Wahy and Waqf-Based Scientific Research Funding: Toward a Sustainable Framework for Knowledge Production and Human Development - Zulaihat Mohammed Yakubu; Adamu Abubakar Muhammad; Ahmad Babikir; Asmau Muhammad Saad; Ibrahim Isa Bello; Shaaban Idris Abdullahi; Bilyaminu Yusuf; Abdullah A. Afifi (IDRIS Darulfunun Institute, 2026)
Scientific research is central to knowledge advancement, innovation, human wellbeing, and civilizational development, yet many research systems face persistent challenges of inadequate and unsustainable funding, institutional capacity, and research autonomy. Historically, waqf supported educational institutions, libraries, healthcare, and scholarly activities, but its potential as a contemporary mechanism for sustainable scientific research remains insufficiently explored. This study examines the potential integration of Maq??id al-Wa?y and waqf-based funding as an institutional framework for sustainable scientific research and knowledge production. A qualitative conceptual and analytical approach was employed through a critical review of classical and contemporary Islamic scholarship on Maq??id al-Wa?y, waqf, Islamic philanthropy, and contemporary research and innovation systems. The findings indicate that waqf can serve as a sustainable and complementary source of research funding when supported by effective governance, professional management, transparent allocation mechanisms, and clearly defined developmental objectives. The study consequently proposes a Maq??id al-Wa?y–Waqf Research Funding Framework for supporting interdisciplinary research in areas such as artificial intelligence, health sciences, environmental sustainability, biotechnology, digital technologies, and education. The framework emphasizes collaboration among researchers, universities, research institutions, policymakers, philanthropists, religious organizations, industry, and communities. The study contributes conceptually by repositioning waqf from predominantly charitable expenditure toward long-term social investment in knowledge production and innovation, while providing a revelation-centred ethical orientation for research directed toward human wellbeing and sustainable development. As a conceptual study, the framework requires empirical validation through future institutional, comparative, and field-based research.